KULTUR PESANTREN MODERN: INTEGRASI SISTEM MADRASAH DAN PESANTREN DI PONDOK MODERN GONTOR - Moh. In’ami (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article describes and analyzes in]tegrity of school and boardingschool cultural system. The data is collected using observation, interviewand observation. In Gontor Boarding School, the students studyseveral subjects which are combined with religious knowledge. The boardingschool itself designs the learning system as a tool by giving someobligation to the students.